2013
DOI: 10.1021/jm301769u
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxypyridin-2-thione as Novel Zinc Binding Group for Selective Histone Deacetylase Inhibition

Abstract: Small molecules bearing hydroxamic acid as the zinc binding group (ZBG) have been the most effective histone deacetylase inhibitor (HDACi) to date. However, concerns about the pharmacokinetic liabilities of the hydroxamic acid moiety have stimulated research efforts aimed at finding alternative non-hydroxamate ZBGs. We have identified 3-hydroxypyridin-2-thione (3-HPT) as a novel ZBG that is compatible with HDAC inhibition. 3-HPT inhibits HDAC 6 and HDAC 8 with an IC50 of 681 nM and 3675 nM respectively. Remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 54 publications
3
70
0
Order By: Relevance
“…Combination with a tolyl linker, Nbonded a,b-unsaturated, or aromatic substituents greatly enhanced activity and selectivity [2,14]. Concerns about pharmacokinetic properties of the HA moiety stimulated scientists to find alternative zinc binding groups (ZBGs) [24]. Thiols, a-ketoesters, electrophilic ketones, mercaptoamides and phosphonates, and 3-hydroxypyridin-2-thione ( Figure 2) are novel ZBGs for selective HDAC6 inhibition in the submicromolar range [24].…”
Section: Structure Of Hdaci and Achievement Of Specificity For Hdac6mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination with a tolyl linker, Nbonded a,b-unsaturated, or aromatic substituents greatly enhanced activity and selectivity [2,14]. Concerns about pharmacokinetic properties of the HA moiety stimulated scientists to find alternative zinc binding groups (ZBGs) [24]. Thiols, a-ketoesters, electrophilic ketones, mercaptoamides and phosphonates, and 3-hydroxypyridin-2-thione ( Figure 2) are novel ZBGs for selective HDAC6 inhibition in the submicromolar range [24].…”
Section: Structure Of Hdaci and Achievement Of Specificity For Hdac6mentioning
confidence: 99%
“…Concerns about pharmacokinetic properties of the HA moiety stimulated scientists to find alternative zinc binding groups (ZBGs) [24]. Thiols, a-ketoesters, electrophilic ketones, mercaptoamides and phosphonates, and 3-hydroxypyridin-2-thione ( Figure 2) are novel ZBGs for selective HDAC6 inhibition in the submicromolar range [24]. Intriguingly, potent and selective inhibition of HDAC6 in the nanomolar range by a 'capless' small molecule inhibitor is possible [25].…”
Section: Structure Of Hdaci and Achievement Of Specificity For Hdac6mentioning
confidence: 99%
“…24 We observed that aryl- and diaryl-analogs of these 3HPT-derived HDACi have selective inhibitory activity against HDAC6 or HDAC8 but are otherwise inactive against HDAC1. We envisioned that these 3HPT-derived compounds could constitute useful molecular probes for parsing out the contribution of inhibition of classes I and II HDACs to the antileishmanial activity of HDACi.…”
mentioning
confidence: 92%
“…Recent reports of 3-hydroxypyridine-2-thiones as selective HDAC inhibitors against HDAC 6 and 8 but not HDAC 1 further motivate the disclosure of our study. 25,26 Previously reported 1HPT analogues 24 with single amino acid (1-2) and their synthetic precursor (1HPT-6-carboxilic acid, 3)…”
mentioning
confidence: 99%